EVALUASI PELAKSANAAN TUGAS PEMERINTAH DESA DALAM PENYELENGGARAAN PEMBANGUNAN FISIK DI DESA PONDOK KELOR KECAMATAN SEPATAN TIMUR KABUPATEN TANGERANG - Junaedi, Junaedi; Mulyono , Doddy (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to analyze the physical development process in Pondok Kelor Village, focusing on the planning, implementation, and the impact of these developments on the community. A qualitative approach with in-depth interviews was conducted with informants, including village officials, community leaders, and residents directly involved in the development process. The data collected was then analyzed to describe how the community participated in the planning, implementation, and monitoring of physical development in the village. The findings of the study indicate that the physical development planning process in Pondok Kelor Village is participatory, conducted through village meetings that involve the community in determining development priorities. The implementation of development is well-managed with transparent supervision, though challenges such as funding constraints and limited time have been encountered. The physical infrastructure improvements, including roads, bridges, and public facilities, have positively impacted the mobility of residents and economic activities. The long-term effects of this development include improved quality of life, better accessibility, and enhanced access to public services. Based on these findings, this study recommends increasing community involvement in all stages of development, particularly in monitoring and maintaining infrastructure. Additionally, it is important to strengthen transparency and accountability in budget management and improve the capacity of village officials in project management. This research is expected to serve as a reference for village administrators and relevant parties in designing and implementing more effective and sustainable physical development.